Pengenalan Potensi Budaya Lokal (Rokat Tase’) Melalui Pendekatan PM3 - Abd Azis; Mufti Syaifuddin (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2020)
Abstrak Local potential object (Rokat tase') Is one of the great natural treasures That we can be proud of and grateful for. Every place in sumenep has well-traveled Tours in terms of the beauty of the place, the coolness of both its customs and its customs.While the local government has declared an economic locomotive for the region to be of no significant value,Due to many obstacles. Sumenep has many local Tours both religious and daily, but there are still a lot of tourists who still don't know,It is therefore necessary to inform the public about the potential for local tourism in sumenep.One approach is the introduction of potential local tourism through PM3 approaches.In this study focuses how students and youth easily get to know, know and visit to know the local culture.The method is established by media graphics (pictures or photos). Resources in this study are local images and programs of culture (rokat tase') that are in Aeng Panas.The documentary study data collection, and the main image collectors in the study are cell phones and digital cameras,Research shows that exposure to the local cultural AENG PANAS potential of through PM3 learners is easy to enjoy and understood by the students and youth of the AENG PANAS Village and outside even the district level.